The Korea-Russia trade activation with the Arctic sea route cooperation (International relations and international law Journal, 2020)
The potential for development in the Arctic Circle is wide and it is fully predictable that the developmentof resources in the region will accelerate further exploration of the Arctic sea route. Russia isshowing high interest in developing resources that are not in the economic sanction list. Moreover, theexploration and utilization of the so-called Arctic sea route across the regional ocean is recently receivingmassive attention along with the climate change. Korea and Russia have expanded the economiccooperation and now the two countries are looking for a new model of the work. They can share thegoals through the further development of Russian Arctic Circle with the rapid exploitation of resourcesdue to climate change and technological development. Korean companies have begun to bring the realeconomic benefits, having positive effects on related industries such as the construction of transport andspecial ships. There are many ways for realizing the goal, but we can specifically propose a Korea-RussiaFTA. In the process of pursuing it, the government should also consider various tasks, such as harmonizingwith the FTAs Korea has been signing, and dealing with the domestic law in accordance with thenew FTA, based on the previous experiences. From Russia’s point of view, special circumstances suchas the EAEU should be taken in consideration. The process of signing the FTA, which will serve as theinternational legal basis for cooperation between the partners, should be clearly marked for the purposeof ‘Sustainable Arctic Development’. Furthermore, these propositions should be able to be digested inthe process of utilizing FTAs and readjusting domestic and international regulations, as well as the jointrespond to the emergence of new industries, markets, and even unforeseen issues. In Korea’s perspective,it should consider the possibility that the FTA could be used in non-economic areas such as on theKorean Peninsula issue.Key words: Korea, Russia, Arctic Circle, Arctic Sea Route, Free Trade Agreement (FTA), EurasianEconomic Union (EAEU).